MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MENCOCOK ANAK USIA 4-5 TAHUN DI PAUD MUSLIMAT NU KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Hasanah, Siti Nurul; ', Zulirfan; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in the fine motor skill in children age 5-6 years through pricking activity in kindergarten Muslimat NU Tapung Hulu District Regency Of Kampar. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 5-6years are numbered 10 children in early childhood Muslimat NU. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that the pricking activity can improve fine motor skill in children aged 5-6 years. It can be seen from the increase in the average percentage of the fine motor skill children in the first cycle of 52,5% which is the criterion developing according to expectations (BSH) and an increase of 34,51% in the second cycle be 75,6% which is very good at developing criteria (BSB). So, pricking activity can improve fine motor skills of children aged 5-6 years in early childhood Muslimat NU Tapung Hulu District Regency Of Kampar.